TINGKAT KEMAMPUAN SOFT SKILLS FUNGSIONARIS LEMBAGA KEMAHASISWAAN FAKULTAS ILMU KEOLAHRAGAAN UNIVERSITAS NEGERI SEMARANG ANGKATAN 2009 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
The purpose of this study was to determine the level of soft skills functionaries Student Organizations Faculty of Sport Science , State University of Semarang 2009.Sampling in this study used purposive sampling technique that uses a sample of 83 students who take the class of 2009 student organizations . The author uses descriptive quantitative research methods with the method of the survey , and collection of information or data using questionnaires , the study took a sample of the population and the use of questionnaires as a data collection tool.Based on the results of data processing , obtained the soft skills that students can be described as follows : for 36 students ( 43.37 % ) in the high category , by 47 students ( 56.63 % ) in the medium category , for 0 students ( 0 % ) in low category Referring to the results of the study concluded that the level functionaries Soft Skills Student Organizations School of Sport Science , State University of Semarang Force 2009 in the category of being.